1988
DOI: 10.1159/000124960
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Angiotensin Acts at the Subfornical Organ to Control the Activity of Paraventricular Nucleus Neurons with Identified Projections to the Median Eminence

Abstract: The present studies were carried out to investigate the mechanisms through which systemic angiotensin II (AII) acts within the central nervous system to influence the release of anterior pituitary hormones in the Sprague-Dawley rat. In particular, these studies have examined the role of the subfornical organ (SFO) as an essential structure mediating these responses. Extracellular single-unit recordings were obtained from 199 paraventricular nucleus (PVN) neurons anti-dromically identified as projecting to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Neurons in the CVOs, notably the subfornical organ (SFO) and the organum vasculosum of the lamina terminalis (OVLT), not only sense circulating peptides like ANG II (3,14) but also send ANG II-immunoreactive efferent projections to the PVN where neurons express a high concentration of ANG II AT 1 receptors (23,29). Electrophysiological studies demonstrate that ANG II can increase PVN unit discharge when applied either directly within the SFO or when given systemically (1,15). Together, available evidence indicates that ANG II is a likely neurotransmitter released from SFO terminals within the PVN (22,41).…”
Section: Discussionmentioning
confidence: 99%
“…Neurons in the CVOs, notably the subfornical organ (SFO) and the organum vasculosum of the lamina terminalis (OVLT), not only sense circulating peptides like ANG II (3,14) but also send ANG II-immunoreactive efferent projections to the PVN where neurons express a high concentration of ANG II AT 1 receptors (23,29). Electrophysiological studies demonstrate that ANG II can increase PVN unit discharge when applied either directly within the SFO or when given systemically (1,15). Together, available evidence indicates that ANG II is a likely neurotransmitter released from SFO terminals within the PVN (22,41).…”
Section: Discussionmentioning
confidence: 99%
“…The subfornical organ sends a dense, angiotensin II-containing projection to the paraventricular nucleus (14), and angiotensin II-binding sites are concentrated along this pathway (15). It seems likely, therefore, that subfornical organ-paraventricular nucleus projection is at least one source for angiotensin II that binds to angiotensin receptors in the paraventricular nucleus and that this connection mediates the effects of circulating angiotensin II in the control of pituitary function (9,12).Angiotensin receptors are increased after repeated stress in the paraventricular nucleus and subfornical organ (16) and after dehydration in the subfornical organ (17). Increased concentration of circulating angiotensin II might upregulate its own receptors in stress and dehydration by a mechanism similar to that described for peripheral angiotensin receptors (18).…”
mentioning
confidence: 99%
“…Vasopressin release is increased by central (10) and perhaps also by peripheral (11) administration of angiotensin II. Peripheral angiotensin II administration stimulates ACTH release from the anterior pituitary gland (12), but this effect may be mediated through the brain angiotensin II system: circulating angiotensin II may bind to receptors in circumventricular organs and stimulate the brain angiotensin II system, which leads to increased ACTH release probably through the stimulation of corticotropinreleasing hormone (CRH) secretion from the hypothalamus (9,12).…”
mentioning
confidence: 99%
“…Electrophysiological studies have confirmed that circulating ANG II affects sympathetic premotor neurons in the PVN, some of which are associated with cardiovascular changes induced by ANG II locally (15). These PVN premotor neurons project to the RVLM, an area that is involved in cardiovascular regulation (11,23,26,30,35,40).…”
Section: Discussionmentioning
confidence: 93%